Competence as a Full Mediator: Unravelling the Indirect Path from Training to Teacher Performance in Vocational High Schools - Nia Meitisari; F.X. Parama Santati; Nyimas Dewi Murnila Saputri (Universitas Bina Sarana Informatika, 2026)
This study examines the relationship between training and competence, and its direct and indirect influence on performance. Competence serves as a mediating variable in the relationship between training and performance. The type of this research is a quantitative study, with a research instrument using a questionnaire. The population in this study amounted to 2,007 teachers from public and private vocational high schools in Palembang. This research sample used a probability sampling technique, namely proportionate stratified random sampling. The sample size used is based on the Slovin formula. From 181 questionnaires collected, the data obtained were then analyzed using SEM (Structural Equation Modeling) PLS. The results of this study indicate that the training has not significantly influenced teacher performance; meanwhile, training has a positive and significant influence on competence, and competence has a positive and significant influence on teacher performance. In addition, the results of this study also show that the competence variable fully mediates the improvement in teacher performance. The path coefficient of 0.186 with a t-statistic of 2.663 (≥ 2.58) indicates a highly significant indirect effect, showing a positive but relatively weak-to-moderate influence that remains meaningful.